2020
DOI: 10.1177/1533033820909829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Prognosis in Nasopharyngeal Cancer Using Machine Learning

Abstract: Background and Aim: Although the prognosis of nasopharyngeal cancer largely depends on a classification based on the tumor-lymph node metastasis staging system, patients at the same stage may have different clinical outcomes. This study aimed to evaluate the survival prognosis of nasopharyngeal cancer using machine learning. Settings and Design: Original, retrospective. Materials and Methods: A total of 72 patients with a diagnosis of nasopharyngeal cancer who received radiotherapy ± chemotherapy were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Right-censored data are quite common in cancer survival analysis, which means that follow-up ends before subjects experience a specific event, such as disease progression. As mentioned above, there are several studies that applied ML techniques for cancer prognosis prediction [ 16 , 17 , 18 , 19 , 20 ]. However, many ML approaches have an assumption that all patient outcomes are known (disease progression or no disease progression).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Right-censored data are quite common in cancer survival analysis, which means that follow-up ends before subjects experience a specific event, such as disease progression. As mentioned above, there are several studies that applied ML techniques for cancer prognosis prediction [ 16 , 17 , 18 , 19 , 20 ]. However, many ML approaches have an assumption that all patient outcomes are known (disease progression or no disease progression).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also compared the performances of the three models using the log-rank test by stratifying the testing set into high- and low-risk groups. Many similar studies in the past only adopted conventional metrics, such as accuracy and AUROC [ 16 , 17 , 18 , 19 , 20 ], which are not suitable for censored data. Moreover, to the best of our knowledge, this study is the first one to compare CPH, CSF, and DeepSurv using three different evaluation metrics in NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall performance of the DenseNet model was noted with the average sensitivity of 95%. In [10] Melek akcay et al, proposed an automated machine learning model to evaluate the prognosis of nasopharyngeal cancer. The study was conducted with 72 patients who are diagnosed with nasopharynx cancer and undergone chemotherapy with proper follow ups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…circHIPK3 and nasopharyngeal carcinoma (NPC). NPC is a common malignant tumor in humans, which occurs in the head region (74). In 2018, Ke et al (75) revealed that circHIPK3 expression was higher in NPC tissues and cell lines compared with in normal tissues and cells.…”
Section: Circhipk3 and Human Diseasesmentioning
confidence: 99%